Anti-Inflammatory and Gastroprotective Evaluation of Prodrugs of Piroxicam. (26th August 2014) - Redasani, Vivekkumar K.; Shinde, Amol B.; Surana, Sanjay J.
Abstract : Therapeutically potential prodrugs of piroxicam were synthesized by effective masking of enolic hydroxyl group through generation of ester congeners. The reaction facilitated using N, N′-dicyclohexylcarbodiimide coupled with acetic acid, benzoic acid, p-toluic acid, m-toluic acid, and cinnamic acid. Synthesized prodrugs were characterized for confirmation of the said structures. The modification of piroxicam showed better anti-inflammatory activity as evoked by all prodrugs. Interestingly, compound3e, cinnamic acid ester prodrug, depicted 75 percent inhibition of rat paw edema as compared to 56 percent for parent piroxicam at 6 h of study. The present work proves the applicability not only with increased anti-inflammatory activity, but also with marked attenuation in ulcerogenicity. Novel prodrug3e, cinnamic acid derivative, was found to be the least ulcerogenic having ulcer index of 0.67 as compared to parent drug piroxicam with 2.67.